Simple Controlling Ecofriendly Synthesis of Silver Nanoparticles at Room Temperature Using Lemon Juice Extract and Commercial Rice Vinegar - T. Lan Anh Luu; X. Truong Cao; V. Thai Nguyen; N. Linh Pham; H. Lam Nguyen; C. Tu Nguyen (Journal of Nanotechnology)
Silver nanoparticles were prepared in an ecofriendly manner at room temperature via the stepwise-modified Tollens route using the lemon juice extract and commercial rice vinegar. In this work, the lemon juice extract—a natural-origin chemical—was used as a reducing and stabilizing agent, and commercial rice vinegar was used to create a low acidic environment to control the silver nanoparticle growth via the stepwise method. The average dimension of silver nanoparticles was qualitatively evaluated through the UV-Vis spectra via the Mie theory. The X-ray diffraction and field emission scanning electron spectroscopy were employed to study the purity, the crystal structure, and the morphology of samples, respectively. Due to the weak activity and low purity of ecofriendly chemicals, the reaction and baking times strongly affect the preparation efficiency in obtaining small-size silver nanoparticles (∼40 nm). The highest efficiency was obtained with 24 h reaction time and 48 h baking time. The bimodal distribution of the size of silver nanoparticles was observed by UV-Vis analysis and field emission scanning electron microscopy. The obtained small-size silver nanoparticles (∼40 nm) have a uniform dimension. The quality of the obtained silver nanoparticles was evaluated through the conducting properties of silver paint made from ecosynthesized silver nanoparticles which showed a promising prospect to develop green-synthesized silver paint working at room temperature.